Export Credit Guarantees and Export Performance: An Empirical Analysis for Germany - Gabriel J. Felbermayr; Erdal Yalcin (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
Recent literature finds that exporters are particularly vulnerable to financial market frictions.As a consequence, exports may be lower than their efficient levels. For this reason,many countries support exporters by underwriting export credit guarantees. The empiricalevidence on the effects of those policies is, however, very limited. In this paper, we usesectoral data on export credit guarantees issued by the German government. We investigatewhether those guarantees indeed do increase exports, and whether they remedy the exportrestrictingeffect of credit market imperfections both on the sectoral and on the exportmarket levels. Exploiting the sectoral structure of a rich three-ways panel data set ofGerman exports, we control for unobserved heterogeneity on the country-year, sectoryear,and country-sector dimensions. We document a robust export-increasing effect ofguarantees. There is some evidence that the effect is larger for export markets with poorfinancial institutions and in sectors that rely more on external finance.
Keywords: F10; F14; F36; G20; G28; G32; 330; Financial development; credit constraints; gravity equation; financial crisis; Exportgarantie; Wirkungsanalyse; Exportindustrie; Export; Kreditrationierung; Finanzmarktkrise; Deutschland